Comprehensive analysis of antimicrobial resistance dynamics among broiler and duck intensive production systems - Zsombor Szoke; Peter Fauszt; Maja Mikolas; Peter David; Emese Szilagyi-Tolnai; Georgina Pesti-Asboth; Judit Rita Homoki; Ildiko Kovacs-Forgacs; Ferenc Gal; Laszlo Stundl; Levente Czegledi; Aniko Stagel; et al. (Scientific Reports)
Abstract Antimicrobial resistance (AMR) is a global health challenge requiring cross-sector action, with research largely focused on chickens, leaving ducks underexplored. This study examines AMR dynamics in Ross 308 broilers and Cherry Valley ducks over 15 months and 15 stocking periods under consistent rearing conditions. A total of 96 pooled samples were collected: 50 from broiler farms (26 biological, 24 environmental) and 46 from duck farms (24 biological, 22 environmental). Using next-generation shotgun sequencing, 3,665 distinct AMR types were identified: 1,918 in broilers and 1,747 in ducks. Host-specific AMRs comprised 25.3% in broilers and 18% in ducks, while 56.7% were shared. AMR diversity declined across production phases, with broilers losing 641 types and ducks losing 308, yet AMR frequencies increased significantly by the finisher phase (p < 0.0001). Based on in silico data, prophylactic antibiotic use significantly reduced the prevalence of multidrug-resistant bacteria in both poultry species (p < 0.05). Hospital-acquired infection-associated AMRs were higher in broilers than in ducks at the start of production but declined significantly by the end of the rearing period (p < 0.0001). Above-average resistance markers accounted for approximately 10% of all detected resistance determinants. Tetracycline and phenicol resistances emerged as the most prevalent. 13 high-resistance carrier (HRC) species were shared between both hosts. Broiler-specific HRCs exhibited significantly higher abundances (relative frequency: 0.08) than duck-specific HRCs (relative frequency: 0.003, p = 0.035). The grower phase emerged as a critical intervention point. In farm environments 15 broiler-specific and 9 duck-specific biomarker species were identified, each strongly correlated with poultry-core HRCs (correlation coefficient > 0.7). Broiler exhibited higher abundances of key resistance genes, with tetracycline resistance predominantly associated with Bacteroides coprosuis, Pasteurella multocida, and Acinetobacter baumannii. Despite its limitations, this research provides key insights into AMR trends in two major poultry types, guiding targeted interventions and sustainable management strategies.